The amazing anti-type 2 diabetic drugs in neurodegeneration: the impact of exendin-4, liraglutide and linagliptin in type 2 diabetes, Alzheimer disease and Parkinson disease - Candeias, Emanuel Monteiro (2021)
Tese de Doutoramento em Biologia Experimental e Biomedicina / área Neurociências e Doença apresentada ao Instituto de Investigação Interdisciplinar da Universidade de Coimbra.